Organizing women workers in the informal economy : beyond the weapons of the weak - Kabeer, Naila; Sudarshan, Ratna M.; Milward, Kirsty (Feminisms and development., 2013)
Organizing Women Workers in the Informal Economy explores the emergence of an alternative repertoire among women working in the growing informal sectors of the global South: the weapons of organization and mobilization. This crucial book offers vibrant accounts of how women working on farms, as sex workers, maids, and waste pickers, in fisheries and factories, have come together to carve out new identities for themselves, define what matters to them, and develop collective strategies of resistence and struggle. -- Book Jacket.